Revitalisasi Perpustakaan: Meningkatkan Literasi Dan Pengetahuan Masyarakat Desa Sijantang Koto, Kota Sawahlunto - Yummi Meirafoni; Selpi Angraini; Farid Athallah Afriani; Silvia Azahra; Ahmad Nur Qodri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The revitalization of libraries in Sijantang Koto Village, Talawi District, Sawahlunto City, is a strategic step to improve the quality of human resources through a literacy approach and strengthening reading culture. The revitalization of the village library aims to revive the village library as a strategic tool that aims to improve the literacy and knowledge of the village community. This study examines steps to revive the function of village libraries. The revitalization process is carried out with three aspects, namely; arrangement of library rooms, addition of collections and classification of books or numbering of openings and making literacy programs in the form of reading corners. The method used is Participatory Actions Research (PAR) which emphasizes on encouraging positive change for the community through observation, interviews, and data collection approaches to gain an understanding of the needs and potentials of the community in accessing knowledge. Therefore, the village library not only serves as a place to store books, but also as a center for community empowerment that focuses on improving educational knowledge